(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
In this article, our objective is to present which discursive formations, as defined by the French philosopher Michel Foucault in his work The Archeology of Knowledge (1969), were present in Brazilian and Portuguese printed journalism regarding Russia’s military action unleashed on Ukrainian territory in February 24, 2022. This concept will also be discussed in light of the redefinitions of Michel Pêcheux, a French Discourse Analysis theorist, who gave new contours to the Foucauldian notion. We analyzed 16 newspaper covers (eight Brazilian and eight Portuguese) published the day after the start of Russian actions in Ukraine. Our reading observes the support of Portuguese media outlets for the Ukrainian cause and the demonization of Russian President Vladimir Putin as responsible for the outbreak of the conflict; In the Brazilian case, the discursive formation around the war is very present, but Putin is part of a discursive formation distinct from that operated in Portugal.